Publisher Correction: Single-cell profiling of breast cancer T cells reveals a tissue-resident memory subset associated with improved prognosis. (December 2018) - Savas, Peter; Virassamy, Balaji; Ye, Chengzhong; Salim, Agus; Mintoff, Christopher; Caramia, Franco; Salgado, Roberto; Byrne, David; Teo, Zhi; Dushyanthen, Sathana; Byrne, Ann; Wein, Lironne; et al.
In the version of this article originally published, the institution in affiliation 10 was missing. Affiliation 10 was originally listed as Department of Surgery, Royal Melbourne Hospital and Royal Womens' Hospital, Melbourne, Victoria, Australia. It should have been Department of Surgery, Royal Melbourne Hospital and Royal Womens' Hospital, University of Melbourne, Melbourne, Victoria, Australia. The error has been corrected in the HTML and PDF versions of this article.